Budaya Austronesia Di Indonesia Bagian Barat Dalam Kaitannya Dengan Migrasi Out Of Taiwan - Ketut Wiradnyana (Berkala Arkeologi Sangkhakala, 2015)
Out of Taiwan is one of the theories about the dispersion of the Austronesian people, which is the most popular among the researchers who study the Austronesian people and culture until now. The theory’s popularity is supported by linguistic, anthropological, DNA, and dating, as well as archaeological data. The quite abundant archaeological data has contributed to the existence of the theory, among others the hypothesis about the dispersion of quadrangular adzes and rounded axes. The migration based on reveals human migration route from the Philippines to Sulawesi (Celebes), and from Sulawesi it was split into two directions, one of which went westward to Kalimantan (Borneo) and moved on to Sumatra, Java, Bali, and East Nusa Tenggara. The other route was to the eastern part of Indonesia. The route to the west is associated with quadrangular adze distribution, while the one to the eastern part of Indonesia is associated with round axe distribution. Furthermore, the red-slipped pottery was initially existed only in the eastern part of Indonesia, which led to a hypothesis that its distribution was limited to that region. But later the red-slipped pottery was also found in the western part of Indonesia, which indicates that there was human migration from the Austronesian place of origin (Southern China) to West Indonesia. In accordance with the migration route to the western part of Indonesia, and based on information obtained from excavations at a number of sites in that area, as well as carbon analyses and other analyses using descriptive qualitative method with inductive reasonings, there is an increasingly strong indication that there were migrations of Prehistoric Austronesian speakers, which tend to be different from the Out of Taiwan migration route. Naskah